Evaluation of Contraindicated Drug-Drug Interactions in Electronic Health Insurance Data at 3 Hospitals in Quang Ninh Province through Navicat Software - Thanh Hai, Nguyen; Thi Thu Ha, Pham; Thanh Long, Do; Thi Van, Duong; Xuan Bach, Nguyen (VNU Journal of Science: Medical and Pharmaceutical Sciences, 2021)
This study analyzes contraindicated drug-drug interactions stored in electronic health insurance data at three hospitals in Quang Ninh Province based on the list of concentrated contractor drugs applied in Quang Ninh province within the scope of payment of the Health Insurance Fund in 2018. The researchers developed a list of 112 pairs of the contraindicated drug-drug interactions to serve as a reference to determine the frequency of contraindicated drug-drug interactions over 519,500 medical records and 1,254,099 prescriptions at 3 hospitals in Quang Ninh province. Twenty-six contraindicated drug-drug interactions (0.006%) were found over 297 medical records and 789 prescriptions; 5 pairs with the highest frequency are: Amiodarone-Amitriptyline, Amiodarone-Moxifloxacin, Amiodarone-Colchicine, Levodopa -Sulpiride, and Amiodarone-Haloperidol. Medical reccords with contraindicated drug-drug interactions were found in 13 different departments or interdisciplinary departments at all the three hospitals, of which the highest rates were found in Intensive Care Unit and Emergency Departments (24.2%), Endocrinology Departments (16.2%) and Cardiology Pediatric Departments (10.4%). The study also analyzed 26 pairs of common contraindicated drug-drug interactions in clinical practice based on retrospective data on drugs prescribed at the 3 hospitals in Quang Ninh Province. Keywords Contraindicated drug-drug interactions, hospitals in Quang Ninh province, medication review tools. References [1] D.C. Malone, J. Abarca, P.D. Hansten, A.J. Grizzle, E.P. Armstrong, R.C.V Bergen, B.S. Duncan-Edgar, S.L. Solomon, R.B. Lipton, Indentification of Serious Drug-Drug Interactions: Results of the Partnership to Prevent Drug-Drug Interactions, J. Am. Pharm. Assoc. 44 (2004) 142-151. https://doi.org/10.1331/154434504773062591. [2] P. Vonbachl, A. Dubied, S. Kra¨henbu¨hl, J.H.Beer, Evaluation of frequently used drug interaction screening programs, Pharm. World. Sci. 30 (2008) 367-374. https://doi.org/10.1007/s11096-008-9191-x. [3] N.T. Hanh, V.T.P. Thao, H.Q. Tuan, N.X. Bach, N. T. Hai, Developing a list of important drug-drug interactions in the clinical practice in the internal department – Kien An Hospital, Hai Phong City, VNU Journal of Science: Medical and Pharmaceutical Sciences, 35(2) (2019) 54-67. https://doi.org/10.25073/2588-1132/vnumps.4179. [4] L.H. Duong, Developing clinically signification drug-drug interactions at Hop Luc General Hospital (2017), Specialist Pharmacist Graduation thesis – 1st Class, Ha Noi University of Pharmacy (in Vietnamese). [5] L.T. Phuong, Managing clinically signification drug-drug interactions at the National Geriatric Hospital (2018), Pharmacist Graduation thesis, Ha Noi University of Pharmacy (in Vietnamese). [6] T.T. Hoai, Examining drug-drug interactions in the inpatient medical records at the Thai Nguyen Lung Hospital (2017), Specialist Pharmacist Graduation thesis – 1st Class, Ha Noi University of Pharmacy (in Vietnamese). [7] Ministry of Health, Vietnam Regulatory Affairs Society, Medical Publishing House one member Company Limited, Vietnam, 2015 (in Vietnamese). [8] A.P. Heverton, R.L.P Leonardo, M.V Carlos, F.F.C. Maria, Patient’s lack of understanding producing insulin drug-interactions in Southeast Brazilian primary care clinics, Diabetes & Metabolic Syndrome: Clinical Research & Reviews. 3(2) (2019) 1131-1136. https://doi.org/10.1016/j.dsx.2019.01.032